A Quasi-Experimental Study Investigating the Effect of Written Corrective Feedback on Students' Writing Accuracy - OUCHAIB, Abdelaziz (International Journal of Linguistics and Translation Studies, 2024)
It has been widely recognized that writing is one of the most critical micro-skills in language teaching and learning. Consequently, numerous researchers in English Language Teaching (ELT) have investigated the impact of written corrective feedback (WCF) on students' writing proficiency. The research on this topic has produced mixed and inconclusive results, indicating a lack of consensus on the efficacy of WCF. This study examines WCF's impact on the writing accuracy of S4 students at the School of Arts and Humanities in Meknes. To achieve this objective, a quasi-experimental case study design was employed. Research instruments included pre-tests and post-tests administered to control and experimental groups to measure students' writing achievements with and without WCF. Additionally, a questionnaire was distributed to 64 students and 30 teachers to explore their preferences for WCF techniques. Semi-structured interviews were also conducted with teachers to identify challenges that prevent them from providing direct WCF. The results indicated that the control group showed lower achievement scores than the experimental group, suggesting a disadvantage in learning writing without WCF. The questionnaire results revealed a mismatch between teachers' and students' preferences for WCF techniques; students preferred direct WCF, while teachers favoured indirect WCF. Insights from the interviews indicated that most teachers are reluctant to provide direct WCF due to large class sizes. In conclusion, this paper offers several pedagogical implications for stakeholders, teachers, and students at the School of Arts and Humanities in Meknes to improve writing skills' teaching and learning.